Clinical Prognosis and Nomograms for Hormone Receptor-Positive and Human Epidermal Growth Factor Receptor 2-Negative Metastatic Breast Cancer Patients Treated with Palbociclib and Endocrine Therapy - Song S; Sun L; Liu X; Zhang L; Li C; Liu Z; Liu F; Yu Z (Breast Cancer: Targets and Therapy)
Shubin Song,1 Luhao Sun,1 Xiaoyu Liu,2 Liang Zhang,1 Chao Li,1 Zhaoyun Liu,1 Fengzhen Liu,3 Zhiyong Yu1 1Department of Breast Surgery, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, Shandong Province, People’s Republic of China; 2Department of Breast and Thyroid Surgery, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong Province, People’s Republic of China; 3Advanced Medical Research Institute and Meili Lake Translational Research Park, Shandong University, Jinan, Shandong Province, People’s Republic of ChinaCorrespondence: Zhiyong Yu, Email zyyu@sdfmu.edu.cn Fengzhen Liu, Email fzliu@sdu.edu.cnBackground: This study aimed to analyze factors affecting the prognosis of patients with hormone receptor-positive (HR+) and human epidermal growth factor 2-negative (HER2-) metastatic breast cancer (MBC) treated with palbociclib and endocrine therapy (ET).Methods: Patients with HR+/HER2- MBC who were treated with palbociclib plus ET between January 2019 and December 2020 at Shandong Cancer Hospital were recruited. Clinicopathological data, treatment outcomes, and survival were from electronic medical system and telephone follow-up.Results: A total of 90 eligible patients were recruited in this study; 55 (61.11%) patients preferred chemotherapy as first treatment, and 35 (38.89%) preferred ET as first treatment. The percentages for 1st, 2nd line, and ≥ 3 lines applying palbociclib were 17.78%, 16.66%, and 65.56%, respectively. In the univariate analysis, multiple factors influenced the primary overall survival (pOS, from initial diagnosis of BC to death), progression-free survival (PFS), and mOS (from diagnosis of metastasis to death). Meanwhile in the multivariate analysis, pPR (progesterone receptor of primary tumor) and prior ET response were independent risk factors for pOS, PFS, and mOS. Lower pPR and prior ET resistance predicted poorer pOS, PFS, and mOS in HR+/HER2- MBC patients. Number of lines of palbociclib application was an independent risk factor for pOS and mOS and presented higher points both in the pOS and mOS nomograms, meaning that palbociclib had a more significant impact on pOS and mOS compared to other factors. The nomograms showed excellent discrimination and prediction accuracy with area under curves (AUC) of 0.974 for pOS, 0.627 for PFS, and 0.881 for mOS, respectively.Conclusion: This real-world single-center study of patients with HR+/HER2- MBC showed that early application of palbociclib combined with ET may bring better PFS, but not pOS and mOS. pPR and prior ET response were independent risk factors affecting prognosis.Keywords: breast cancer, prognosis, palbociclib, endocrine therapy, CDK4/6i